Safety Climate in Organizations - Griffin, Mark; Curcuruto, M. (2016)
© Copyright 2016 by Annual Reviews. Safety climate is a collective construct derived from individuals' shared perceptions of the various ways that safety is valued in the workplace. Research over the past 35 years shows that safety climate is an important predictor of safety behavior and safety outcomes such as accidents and injury. We first review the conceptual foundations of safety climate and explore how the construct can be applied to different levels of analysis. We then review ways that safety climate influences individual processes of sense making, motivation, and work behavior. Next, we explore the impact of safety climate on organization-level outcomes related to both safety and productivity. We conclude with suggestions for future research and practice to support the overall safety of people and organizations.